RANCANGAN SISTEM INFORMASI PENGUKURAN GREEN PRODUCTIVITY DAN ENVIRONMENTAL MANAGEMENT ACCOUNTING UNTUK PENGEMBANGAN USAHA KECIL MENENGAH - Suhartini Suhartini (Prodi Teknik Industri Universitas Muhammadiyah Gresik, 2018)
Batik Kampoeng Jetis is one of the centers batik who have the potential pollution of waste that is high enough so needed an improvement in production process and the management of liquid wastes and solid wastes from the production process. It says quite high because the volume of liquid waste produced by ± 568 m³ per day to produce pieces of batik ± 1400 per day. Batik Kampoeng Jetis also expect the economic benefits of increased productivity resulting from efficient use of resources in order to improve management of the environment. There are two interests, economic interests and the interests of environmental protection. Green Productivity and Environmental Management Accounting are used to accommodate these two interests. Green Productivity is a strategy to increase company productivity and environmental performance simultaneously in the overall social economic development (APO, 2003). Environmental Management Accounting (EMA) is for exploring the costs rather than regard it as an overhead cost. Environmental Management Accounting (EMA) to calculate how much the costenvironment and create an alternative that can provide benefits. The results of this study is to design measurement procedures standardized assessment of Batik Green Productivity for UKM that can ensure sustainability in both the financial and environmental aspects so that they can still survive without ignoring their negative contribution to the environment. Handling of liquid waste that is applied can provide improvements of productivity and environmental performance, although the increase is achieved only 1.3%. But this provides evidence that by implementing Green Productivity and Environmental Management Accounting will be able to increase the productivity and environmental performance.While the profit potential of products that can be achieved by using the Environmental Management Accounting is estimated at 4.4% or Rp.2.194.936.000, - per year.